IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN KARAKTERISTIK AKHLAK PESERTA DIDIK DI MTs IHYAUL ULUM KEDAMEAN GRESIK - Lia Lailatul Fitriyah; Azhar Haq; Adi sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This school has a fairly large number of students, in addition to the strategic location of the school and close to the boarding school, thus making MTs Ihyaul Ulum Kedamean Gresik must be able to support students fully. In the era of globalization, it is possible for students at school to do like skipping school, and fighting with friends. This data source was obtained from the school principal, class teacher, Islamic education teacher, and students. This study uses qualitative methods obtained through observation, interviews, and documentation. using data analysis in the form of data reduction, presentation, and conclusion. The results showed that the learning of Islamic religion at MTs Ihyaul Ulum was quite good because the researchers directly connected Islamic religious education teachers while learning and using learning tools that used learning methods that could help students quickly and quickly what they wanted. and students can be applied in everyday life. Although not carried out optimally, learning activities carried out by Islamic religious education teachers can instill the moral character of students.